2021
DOI: 10.1021/acs.jpcb.0c09144
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Vibrio cholerae Lipid A Types on LPS Bilayer Properties

Abstract: Lipopolysaccharides (LPS) present in the outer leaflet of Gram-negative bacterial outer membranes protect the bacteria from external threats and influence antibiotic permeability as well as immune system recognition. The structure of lipid A, the anchor of an LPS molecule to the outer membrane, can make direct influences on membrane properties. Particularly, in Vibrio cholerae, a Gram-negative bacterium responsible for cholera, a severe diarrheal disease, modifications of lipid A structures grant antibiotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In the presence of a physiological salt concentration, i.e., n 1 ≈ 100 mM, the screening length becomes κ −1 ≈ 10 Å. The following inequality then holds: ϵ w κd/ϵ l ≫ 1, where the dielectric constant of lipids ϵ l ≈ 2 and d ≈ 8 nm (a typical headgroup-headgroup distance for the OM 10 or LPS bilayers 27 ). Under this condition, the electric coupling between the two layers is insignificant.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…In the presence of a physiological salt concentration, i.e., n 1 ≈ 100 mM, the screening length becomes κ −1 ≈ 10 Å. The following inequality then holds: ϵ w κd/ϵ l ≫ 1, where the dielectric constant of lipids ϵ l ≈ 2 and d ≈ 8 nm (a typical headgroup-headgroup distance for the OM 10 or LPS bilayers 27 ). Under this condition, the electric coupling between the two layers is insignificant.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…In the presence of a physiological salt concentration, i.e., n 1 ≈ 100 mM, the screening length becomes κ –1 ≈ 10 Å. The following inequality then holds: ϵ w κd /ϵ l ≫ 1, where the dielectric constant of lipids ϵ l ≈ 2 and d ≈ 8 nm (a typical headgroup-headgroup distance for the OM or LPS bilayers). Under this condition, the electric coupling between the two layers is insignificant. Also the effects of dielectric discontinuities on the LPS surface can be taken into account through the parameter , A natural consequence of this is that the interaction between two charges on the membrane surface is about twice as strong as in the bulk phase.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, antimicrobial peptides (AMPs) have been regarded as promising therapeutics against biofilm-forming pathogens due to their broad-spectrum antibacterial activity and inability to induce resistance (Cardoso et al, 2019;Di Somma et al, 2020;Hancock et al, 2021). Several studies on bacteria in the planktonic state have shown that AMPs adopt a unique membrane-targeting mechanism of action, unlike conventional antibiotics with specific targets, which disturb bacterial membranes mainly by interaction with negatively charged phospholipids and cause cell death (Chen et al, 2020;Li et al, 2020a;Luna et al, 2021). Significantly different from bacteria in the planktonic state, the control of biofilm-encapsulated bacteria is very difficult because of their extremely low permeability to antimicrobial agents (Gilbert et al, 2002;Hall and Mah, 2017).…”
Section: Introductionmentioning
confidence: 99%